Treatment-Related Radiation Toxicity Among Cervical Cancer Patients. Issue 7 (1st September 2018) - Rubinsak, Lisa A.; Kang, Le; Fields, Emma C.; Carter, Jori S.; McGuire, William P.; Temkin, Sarah M.
Abstract : Objective: The purpose of this study is to identify incidence of and factors associated with severe late toxicity in women treated with radiation for cervical cancer. Materials and Methods: All patients with cervical cancer treated with radiation as primary or adjuvant therapy from 2005 to 2017 in a single academic institution were included. Records were reviewed for demographic information, Charlson Comorbidity Index, treatment details, toxicities, and outcomes. Patients with and those without severe late gastrointestinal toxicity (SLGIT), severe late genitourinary toxicity (SLGUT), or any SLGIT or SLGUT, defined as any toxicity (AT), were compared. Overall survival and progression-free survival were also compared. Results: Of 179 patients identified, 21.2% had AT, 17.3% had SLGIT, and 10% had SLGUT. Estimated AT rate at 3 years was 24.2%. The mean duration of follow-up was 37 months (range, 3–146 months). Most patients (84.1%) received 3-dimensional conformal therapy, and 15.9% received intensity-modulated radiation therapy. Factors associated with AT were lower body mass index (24.9 vs 28.3, P = 0.043), white race (63.2% vs 44%, P = 0.035), and active tobacco smoking during treatment (59.5% vs 40.2%, P = 0.036). Any toxicity was not associated with 3-dimensional versus intensity-modulated radiation therapy planning, low-dose versus high-dose–rate brachytherapy or time to complete radiation treatment. Higher total cumulative radiation dose to clinical target volume was associated with SLGIT. Progression-free survival and overall survival were similar among patients with AT compared to those without toxicity. Conclusions: In patients with cervical cancer, radiation toxicity is correlated with lower body mass index, white race, and smoking. Despite technologic advances in radiotherapy planning and delivery, toxicity remains high and interventions to reduce the burden of treatment are needed.